Art and photography - Campany, David (London : Phaidon Press Limited, 2003)
Art and Photography is the first book of its kind to survey the presence of photography in artistic practice from the 1960s onwards. The photographic image is central to contemporary art and the debates that surround it, yet it took most of the last century for it to acquire this status. Despite the extensive exploration of photography as an independent art in the Modernist era, it was not until the late twentieth century that artists, museums and galleries began to explore its social roles as a medium of representation. This volume provides a comprehensive survey of photography's place in recent art history, further contextualized in the Documents section by original artist's statements and interviews, together with critical and theoretical reflections on the photographic and the art of the photograph.
Acconci, Vito ; Adams, Dennis ; Adams, Mac ; Abdu'Allah, Faisal ; Ader, Bas Jan ; Ajamu ; Andre, Carl ; Antin, Eleanor ; Antoni, Janine ; Appelt, Dieter ; Arnatt, Keith ; Baldessari, John ; Baltz, Lewis ; Barrow, Thomas ; Barth, Uta ; Barthes, Roland ; Bate, David ; Baudrillard, Jean ; Becher, Bernd & Hilla ; Benjamin, Walter ; Bernard, Cindy ; Blakely, George ; Blees, Rut ; Blume, Anna & Bernhard Johannes ; Bochner, Mel ; Boltanski, Christian ; Bryson, Norman ; Buchloh, Benjamin H.D. ; Burden, Chris ; Burgin, Victor ; Cadieux, Geneviève ; Calle, Sophie ; Carucci, Elinor ; Casebere, James ; Cavell, Stanley ; Chandra, Mohini ; Close, Chuck ; Cohen, Lynne ; Coleman, James ; Collins, Hannah ; Coplans, John ; Crewdson, Gregory ; Cumming, Donigan ; Cumming, Robert ; Danto, Arthur C. ; Dean, Max ; Derrida, Jacques ; Dibbets, Jan ; diCorcia, Philip-Lorca ; Divola, John ; Doherty, Willie ; Durand, Régis ; Eggleston, William ; Evans, Jason ; Export, Valie ; Fairbrother, Trevor ; Fani-Kayode, Rotimi ; Fischli & Weiss ; Floyer, Ceal ; Fontcuberta, Joan ; Friedlander, Lee ; Fuss, Adam ; Ghirri, Luigi ; Goldin, Nan ; Grace, Della ; Graham, Dan ; Graham, Paul ; Grassie, Andrew ; Greenberg, Clement ; Gursky, Andreas ; Haller, Susan ; Hamilton, Richard ; Hanzlová, Jitka ; Haxton, David ; Heinecken, Robert ; Hernandez, Anthony ; Hilliard, John ; Höfer, Candida ; Horn, Candida ; Horn, Roni ; Huebler, Douglas ; Kennard, Peter ; Knorr, Karen ; Kosuth, Joseph ; Kruger, Barbara ; Lawler, Louise ; Leonard, Zoe ; Levine, Sherrie ; Levinthal, David ; LeWitt, Sol ; Lomax, Yve ; Long, Richard ; Lum, Ken ; Lüthi, Urs ; McMurdo, Wendy ; Mahr, Mari ; Malraux, André ; Mandel, Mike ; Mann, Sally ; Mapplethorpe, Robert ; Matta-Clark, Gordon ; Mendieta, Ana ; Messager, Annette ; Meyerowitz, Joel ; etc.
boek